Explorative Research Course: Recovering Rare Earth Elements from Electronic Waste Using Deep Eutectic Solvents - Banu Kisworo; Ahmad Mudzakir; Liliasari Liliasari; Anna Permanasari (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2023)
This study aims to demonstrate how a course design approach based on explorative research involving systems thinking can be implemented by recovering Rare Earth Elements (REEs) using Deep Eutectic Solvents (DES). The method used in this research is Design-Based Research (DBR). The instruments used were questions regarding the measurement of leaching samples from results/characterization, short questions about concept maps, and student response questionnaires. Data from measurements of leaching samples was measured using a Fourier Transform Infrared Spectrometer (FTIR), data about concept maps was measured by the number of component and process concepts in the context of electronic waste recycling that students were able to identify, and student response data was measured using a Likert scale. Based on the research results, recovery of REEs can be done using DES. It can be shown by a shift in the peak vibration of 497.65 cm-1 from the sample before leaching to a vibration of 449.43 cm-1 after leaching. In addition, this study yields new insights into the perceptions of future pre-service chemistry teachers regarding the possibility of new types of DES in the context of chemistry learning. According to pre-service chemistry teachers, recovering REEs from electronic waste and applying DES are interesting as a new context for laboratory learning. Context-based design of research activities can enhance system thinking and interest in chemistry. The results of study showed increased student’s systems thinking abilities, as shown by the component and process concepts that emerged from the pre-test by 652 concepts while the post-test increased by 1208 concepts.